Distinct decrease in peripheral lymphocytes in EBER-positive cases of MTX-LPD. Issue 1 (2nd January 2021) - Kondo, Masahiro; Murakawa, Yohko; Moriyama, Mayuko; Honda, Manabu; Sugiura, Tomoko; Onoda, Keiichi; Watanabe, Yohei; Kakimaru, Hiroyuki
Abstract: Objectives: To determine the clinical characteristics of methotrexate-associated lymphoproliferative disorder (MTX-LPD). Methods: In this study, 12 RA patients who developed MTX-LPD were assessed. The peripheral blood lymphocyte (PBL) count at the onset of MTX-LPD was compared to that 6 months before the onset, in Epstein-Barr virus-encoded RNA (EBER)-positive and -negative subgroups. We examined the change in the PBL count after MTX withdrawal. In patients with relapsed LPD, changes in the PBL count before relapse were also examined. Results: Regression of LPD after MTX withdrawal was noted in eight patients. In these patients, the PBL count was decreased at the onset of MTX-LPD compared to 6 months before the onset; the decrease was significantly more prominent in EBER-positive patients. In cases of spontaneous regression of LPD, the PBL count recovered quickly after MTX withdrawal. Four of eight patients showed a recurrence of LPD after they improved following MTX withdrawal. These patients also exhibited a decreased PBL count at recurrence compared to 6 months before recurrence. Conclusion: A decrease in the PBL count might be involved in the pathogenesis of MTX-LPD, especially in EBER-positive cases and in patients with LPD relapse after MTX withdrawal following initial improvement.